2021
DOI: 10.3758/s13415-020-00860-y
|View full text |Cite
|
Sign up to set email alerts
|

Imitation or Polarity Correspondence? Behavioural and Neurophysiological Evidence for the Confounding Influence of Orthogonal Spatial Compatibility on Measures of Automatic Imitation

Abstract: During social interactions, humans tend to imitate one another involuntarily. To investigate the neurocognitive mechanisms driving this tendency, researchers often employ stimulus-response compatibility (SRC) tasks to assess the influence that action observation has on action execution. This is referred to as automatic imitation (AI). The stimuli used frequently in SRC procedures to elicit AI often confound action-related with other nonsocial influences on behaviour; however, in response to the rotated hand-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 90 publications
0
5
0
Order By: Relevance
“…Finally, the lack of relationships between the race-IAT and the measures of social cognition that we have employed may be explained by each of these constituent tasks relying on, to a greater or lesser extent, other (non-social) cognitive or attentional processes. Recently it has been shown that the Stimulus Response Compatibility task, which is used commonly to measure imitative tendencies (Cracco et al, 2018), captures more general-purpose cognitive processes deployed in both social and non-social contexts, such as response inhibition and interference resolution (Czekóová et al, 2021;Rauchbauer et al, 2021). Furthermore, Santiesteban et al (2012) provide evidence that the Dot Task relies on the directional rather than agentive features of the task avatar, suggesting that performance on this task may reflect automatic attentional orienting rather than perspective taking per se.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the lack of relationships between the race-IAT and the measures of social cognition that we have employed may be explained by each of these constituent tasks relying on, to a greater or lesser extent, other (non-social) cognitive or attentional processes. Recently it has been shown that the Stimulus Response Compatibility task, which is used commonly to measure imitative tendencies (Cracco et al, 2018), captures more general-purpose cognitive processes deployed in both social and non-social contexts, such as response inhibition and interference resolution (Czekóová et al, 2021;Rauchbauer et al, 2021). Furthermore, Santiesteban et al (2012) provide evidence that the Dot Task relies on the directional rather than agentive features of the task avatar, suggesting that performance on this task may reflect automatic attentional orienting rather than perspective taking per se.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the between‐subject stimulus presentation we employed in our earlier study, only half of the original sample responded to the right stimulus hand oriented counter‐clockwise that we focused on here (RIGHT‐90) – the other half observed a left hand oriented clockwise (LEFT+90). Since we have shown more recently that the latter stimulus elicits both imitative‐ and spatial‐compatibility effects (Czekóová et al ., 2021), we re‐inspected these prior results to determine whether responses differed to each of these stimulus hands. Indeed, while the RIGHT‐90 stimulus elicited a positive compatibility effect (M = 28.35, SE = 2.99 ms), this was reversed for the LEFT+90 (M = −9.17, SE = 3.19 ms) – that is, responses were facilitated by imitatively incompatible actions produced by this latter stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Each block presented one of four different stimulus hands: an actor's right or left hand rotated clockwise (LEFT+90, RIGHT+90) or counter‐clockwise (LEFT‐90, RIGHT‐90) from the participants' perspective. As we have since shown that only the right stimulus hand presented counter‐clockwise isolates imitative from confounding spatial compatibility effects (Czekóová et al ., 2021), we only consider data acquired during the RIGHT‐90 block herein. Note that Catch trials were included in the paradigm only to ensure that participants paid attention throughout the task.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, the lack of relationships between the race-IAT and the measures of social cognition that we have employed may be explained by each of these constituent tasks relying on, to a greater or lesser extent, other (non-social) cognitive or attentional processes. Recently it has been shown that the Stimulus Response Compatibility task, which is used commonly to measure imitative tendencies ( Cracco et al, 2018 ), captures more general-purpose cognitive processes deployed in both social and non-social contexts, such as response inhibition and interference resolution ( Czekóová et al, 2021 ; Rauchbauer et al, 2021 ). Furthermore, Santiesteban et al (2012) provide evidence that the Dot Task relies on the directional rather than agentive features of the task avatar, suggesting that performance on this task may reflect automatic attentional orienting rather than perspective taking per se .…”
Section: Methodsmentioning
confidence: 99%